2008
DOI: 10.1093/aje/kwn230
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Leukemia in Relation to Radio Frequency Electromagnetic Fields in the Vicinity of TV and Radio Broadcast Transmitters

Abstract: A case-control study of radio frequency electromagnetic fields (RF-EMFs) and childhood leukemia was conducted in West Germany. The study region included municipalities near high-power radio and TV broadcast towers, including 16 amplitude-modulated and 8 frequency-modulated transmitters. Cases were aged 0-14 years, were diagnosed with leukemia between 1984 and 2003, and were registered at the German Childhood Cancer Registry. Three age-, gender-, and transmitter-area-matched controls per case were drawn randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Less attention has been paid to the possible relation between RF‐EMF and CL. Only three case–control studies could be identified 39–41. In addition, we found four studies with an ecological design 42–45.…”
Section: Epidemiological Evidence For An Increased Risk Of CL By Expomentioning
confidence: 98%
“…Less attention has been paid to the possible relation between RF‐EMF and CL. Only three case–control studies could be identified 39–41. In addition, we found four studies with an ecological design 42–45.…”
Section: Epidemiological Evidence For An Increased Risk Of CL By Expomentioning
confidence: 98%
“…This contrast may explain some variability in the measurements, since the emissions strongly depend on the spatial orientation of the windows 26. Moreover, objects in the light of sight such as buildings and vegetation, as well as walls in indoor areas have an attenuation effect by orders of magnitude 11 27…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach, although limited to outdoor conditions, is theoretical prediction. Ha et al and Merzenich et al have developed field strength prediction programmes for assessment of individual exposure from AM radio or TV transmitters 10 11. Regarding mobile base stations, much more complex models have been developed to predict field strength at a given location on the basis of the position of the base station, the maximum power load, antenna characteristics, topography, shielding effects of house walls, etc.…”
mentioning
confidence: 99%
“…There is (until September 2010) only one study available for mobile phone use: Elliott et al [16] found no association between risk of early childhood cancers (leukaemia and nonHodgkins lymphoma, cancer of brain and central nervous system) and estimates of the mothers exposure to mobile phone base stations during pregnancy. Furthermore, there are 10 studies investigating brain cancer or leukaemia with respect to EMF emitted from TV or radio transmitters [17][18][19][20][21][22][23][24][25][26]. Only 8 of these transmitter studies, however, present original data.…”
Section: Brain Cancer and Leukaemia: Pro-and Con-argumentsmentioning
confidence: 99%